2023
DOI: 10.1177/20451253231151327
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine and esketamine in suicidal thoughts and behaviors: a systematic review

Abstract: Background: More than 2% of the general population experience suicidal ideas each year and a large number of them will attempt suicide. Evidence-based therapeutic options to manage suicidal crisis are currently limited. Objectives: The aim of this study was to overview the findings on the use of ketamine and esketamine for the treatment of suicidal ideas and acts. Design: Systematic review. Data Sources and methods: PubMed, article references, and Clinicaltrials.gov up to June 30, 2022. Meta-analyses published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…With regard to ketamine, a nasal spray for application of esketamine, the S(+) enantiomer of ketamine, has recently been approved for therapeutic use in several countries, minimizing the risk of substance misuse and side effects such as dissociation ( 75 , 76 ). Although there is strong evidence supporting the positive benefit related to suicide ideation for intravenous racemic ketamine, studies investigating intranasal esketamine did not yet show the same favorable profile ( 77 , 78 ). Given the current lack of empirical evidence, it therefore seems too early to draw conclusions regarding potential effects of esketamine in prison settings.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to ketamine, a nasal spray for application of esketamine, the S(+) enantiomer of ketamine, has recently been approved for therapeutic use in several countries, minimizing the risk of substance misuse and side effects such as dissociation ( 75 , 76 ). Although there is strong evidence supporting the positive benefit related to suicide ideation for intravenous racemic ketamine, studies investigating intranasal esketamine did not yet show the same favorable profile ( 77 , 78 ). Given the current lack of empirical evidence, it therefore seems too early to draw conclusions regarding potential effects of esketamine in prison settings.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, intravenous (IV) ketamine has been shown to reduce, within hours, the suicidal ideation in MDE and BD [11,42,43] (see below).…”
Section: Pharmacological Interventions On Suicidal Behaviormentioning
confidence: 99%
“…We recently published a review article concerning the interest of ketamine in the prevention of suicidal ideation, specifying its clinical interest [11]. It is difficult to model TRD in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have reported on ketamine's effects specifically on suicidality [20], we are aware of only a few studies that have compared how ketamine affects different depression symptoms or symptom clusters [21][22][23]. None of those studies have modeled trajectories of symptoms over time.…”
Section: Introductionmentioning
confidence: 99%